Optical SOA-based switching - Radoslav Odrobinak; Milan Dado; Robert Jankovsky (Communications - Scientific letters of the University of Zilina, 2004)
All-optical switches are fundamental building blocks for high-speed optical networks and basic blocks towards all-optical networks for future communications that utilize Optical Time Division Multiplexing (OTDM) techniques of signal with single channel data rate of hundreds Gbps. It seems that the most promising technology will be based on Semiconductor Optical Amplifiers (SOA). We can arrange these components to some interferometric architectures in which SOAs achieve efficient optical switching rate with low control energy and big optical sampling bandwidth. The interferometric optical switch geometries are presented and characterized in this paper. We discuss their limitation on temporal width of switching window and some of their applications.